1996
DOI: 10.1002/ana.410400309
|View full text |Cite
|
Sign up to set email alerts
|

In vivo mapping of cholinergic terminals in normal aging, Alzheimer's disease, and Parkinson's disease

Abstract: To map presynaptic cholinergic terminal densities in normal aging (n = 36), Alzheimer's disease (AD) (n = 22), and Parkinson's disease (PD) (n = 15), we performed single-photon emission computed tomography using [123I]iodobenzovesamicol (IBVM), an in vivo marker of the vesicular acetylcholine transporter. We used coregistered positron emission tomography with [18F]fluorodeoxyglucose for metabolic assessment and coregistered magnetic resonance imaging for atrophy assessment. In controls (age, 22-91 years), cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
240
1
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(262 citation statements)
references
References 57 publications
16
240
1
5
Order By: Relevance
“…In vivo imaging studies have also shown that the presence of dementia in PD is associated with more severe and widespread cholinergic denervation compared with PD without dementia (Bohnen et al, 2003;Hilker et al, 2005;Kuhl et al, 1996;Shinotoh et al, 1999). These imaging results are consistent with post-mortem evidence that basal forebrain cholinergic system degeneration appears early in PD and worsens in parallel with the appearance of dementia (Ruberg et al, 1986).…”
Section: Heterogeneity Of Cholinergic Denervation In Pd and Clinical supporting
confidence: 74%
“…In vivo imaging studies have also shown that the presence of dementia in PD is associated with more severe and widespread cholinergic denervation compared with PD without dementia (Bohnen et al, 2003;Hilker et al, 2005;Kuhl et al, 1996;Shinotoh et al, 1999). These imaging results are consistent with post-mortem evidence that basal forebrain cholinergic system degeneration appears early in PD and worsens in parallel with the appearance of dementia (Ruberg et al, 1986).…”
Section: Heterogeneity Of Cholinergic Denervation In Pd and Clinical supporting
confidence: 74%
“…In other studies, it was shown that as the disease progresses in AD patients, the levels of VAChT change in a similar fashion and magnitude to other cholinergic marker proteins, in particular choline acetyltransferase, supporting the interest in [ 123 I]-IBVM as an in vivo radioligand for imaging of neurodegenerative disease impairments, such as AD and DLB (Kuhl et al, 1996(Kuhl et al, , 1999. More recently, using […”
Section: C]-pmp [mentioning
confidence: 83%
“…In the cholinergic system, neurons in the NBM are very prone to accumulate neurofibrillary tangles (Mesulam, 2004a,b), such that tangles in this region are also observed in healthy elderly people (Mesulam, 2004b;Sassin et al, 2000). Even in the absence of neuronal loss, the accumulation of such tangles in the NBM can be associated with a decrease in cholinergic neurotransmission as revealed by postmortem counts of cholinergic axons (Geula and Mesulam, 1989) and by in vivo SPECT mapping of cholinergic terminals (Kuhl et al, 1996). In animal studies (e.g., Weible et al, 2004;Woodruff-Pak et al, 2001) and in patients with Alzheimer's disease cognitive improvement can be achieved by nicotinergic as well as muscarinic receptor action (Oh et al, 2005;Raskind et al, 2000;Tariot et al, 2000).…”
Section: Introductionmentioning
confidence: 99%